Conscientiousness dan Dukungan Sosial Teman Sebaya Terhadap Prokrastinasi Akademik Mahasiswa Jurusan Sistem Komputer - Syahrina, Isna Asyri; Muarifah, Alif (Psyche 165 Journal, 2023)
Students who practice academic procrastination often experience failure in the academic field due to the behavior of procrastinating time in doing assignments from lecturers which results in feelings of laziness, fatigue, and boredom so that students experience failure in the academic field. Conscientiousness can be interpreted as a description of a person's persistence to control his inner urges so that he can be responsible and comply with existing norms and rules. Peer social support is needed to reduce academic procrastination behavior, this is because positive support from peers in the educational process will improve student academic performance. This study aims to empirically examine the role of conscientiousness and peer social support in predicting student academic procrastination in the computer systems department of Universitas Putra Indonesia YPTK Padang. The sample for this study was 152 active status students from 2016 to 2019 using a simple random sampling technique. This research is non-experimental quantitative research with a survey method. The research measuring instrument consists of three scales, namely the conscientiousness scale, the peer social support scale and the academic procrastination scale. The results of this study indicate that conscientiousness and peer social support in collaboration are able have a significant effect on student academic procrastination in the computer systems department. Furthermore, conscientiousness partially has a significant effect on student academic procrastination in the computer systems department. Finally, peer social support partially has a significant effect on student academic procrastination in the computer systems department. The relationship that occurs is negative, the higher the conscientiousness and peer social support, the lower the student academic procrastination in the computer systems department.